2015
DOI: 10.3892/or.2015.4167
|View full text |Cite
|
Sign up to set email alerts
|

microRNA-22 downregulation of galectin-9 influences lymphocyte apoptosis and tumor cell proliferation in liver cancer

Abstract: Abstract. plays an important role in both the immune response and tumor progression, while microRNAs act as tumor regulators to mediate tumorigenesis. However, the underlying molecular mechanisms remain unknown. In the present study, we investigated the relationship between Gal-9 and microRNA-mediated regulation in liver cancer. We examined Gal-9 expression using qRT-PCR and western blot analysis and found that it was markedly upregulated in human liver cancer cells compared with the level in normal hepatocyt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(32 citation statements)
references
References 34 publications
1
28
1
1
Order By: Relevance
“…Additionally to the above, miR-22 has been reported to tightly repress cellular immune escape and proliferation and trigger apoptosis by targeting a variety of downstream molecules, such as Galectin-9, NET1 (neuro-epithelial transforming gene 1) and PAPST1, in liver cancer, chronic myeloid leukemia (CML) and medulloblastoma, respectively (2123). In addition, not only could curcumin-induced miR-22 post-transcriptionally degrade oncogene Erbb3 in retinoblastoma, but also ectopic elevated miR-22 expression could directly target Erbb3 or EVI-1, subsequently causing the repression of PI3K/Akt cascade, the end result is inhibition of cellular proliferation, migration, invasion and metastasis in lung cancer and breast cancer, respectively (2426).…”
Section: Mir-22 Work As Suppressor Gene In Tumor Malignant Develomentioning
confidence: 99%
“…Additionally to the above, miR-22 has been reported to tightly repress cellular immune escape and proliferation and trigger apoptosis by targeting a variety of downstream molecules, such as Galectin-9, NET1 (neuro-epithelial transforming gene 1) and PAPST1, in liver cancer, chronic myeloid leukemia (CML) and medulloblastoma, respectively (2123). In addition, not only could curcumin-induced miR-22 post-transcriptionally degrade oncogene Erbb3 in retinoblastoma, but also ectopic elevated miR-22 expression could directly target Erbb3 or EVI-1, subsequently causing the repression of PI3K/Akt cascade, the end result is inhibition of cellular proliferation, migration, invasion and metastasis in lung cancer and breast cancer, respectively (2426).…”
Section: Mir-22 Work As Suppressor Gene In Tumor Malignant Develomentioning
confidence: 99%
“…The target prediction programs miRanda and TargetScan were used to predict and identify miRNAs that may target galectin-9. The present study identified four miRNAs (miR-22, 296-3p, 455-5p and 491-5p) that were potential regulators of galectin-9 (26).…”
Section: Expression Of Candidate Mirnas and Role Of Mir-455-5pmentioning
confidence: 70%
“…Human GAPDH and U6 were used as the housekeeping genes for the amplifications. The PCR primers used in the present study were described previously (26).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Наиболее изученные miR-21 (онкоген) и группа let-7 (микроРНК-онкосупрессоры), изменение экспрессии которых тес-но связано с различными этапами опухолевой прогрес-сии, также регулируют МОБ [84,100,102]. Существуют данные о регуляции флотиллина-1 miR-485 и miR-506 [103,104], флотиллина-2 miR-34а [105] и галектина-3 miR-22 [106]. Вышеупомянутые микроРНК часто об-наруживаются в составе экзосом.…”
Section: регуляция экспрессии микродоменобразующих белковunclassified